2005
DOI: 10.1073/pnas.0501445102
|View full text |Cite
|
Sign up to set email alerts
|

The antiretroviral activity of APOBEC3 is inhibited by the foamy virus accessory Bet protein

Abstract: Genome hypermutation of different orthoretroviruses by cellular cytidine deaminases of the APOBEC3 family during reverse transcription has recently been observed. Lentiviruses like HIV-1 have acquired proteins preventing genome editing in the newly infected cell. Here we show that feline foamy virus (FFV), a typical member of the foamy retrovirus subfamily Spumaretrovirinae, is also refractory to genome deamination. APOBEC3-like FFV genome editing in APOBEC3-positive feline CRFK cells only occurs when the acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
219
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(224 citation statements)
references
References 43 publications
(62 reference statements)
5
219
0
Order By: Relevance
“…The human A3G and muA3 expression constructs (human A3Z2g-Z1c and muA3Z2-Z3) were provided by N. R. Landau (49). Human A3B, -C, -F, and -H (A3Z2A-Z1b, A3Z2b, A3Z2e-Z2f, and A3Z3); feline A3; and canine A3 expression plasmids were previously described (33,44,57,58). Porcine A3 (A3Z2-Z3) was a gift of Eva Dörrschuck and Ralf Tönjes (GenBank accession no.EU871587; E. Dörrschuck et al, unpublished data).…”
Section: Cells and Transfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human A3G and muA3 expression constructs (human A3Z2g-Z1c and muA3Z2-Z3) were provided by N. R. Landau (49). Human A3B, -C, -F, and -H (A3Z2A-Z1b, A3Z2b, A3Z2e-Z2f, and A3Z3); feline A3; and canine A3 expression plasmids were previously described (33,44,57,58). Porcine A3 (A3Z2-Z3) was a gift of Eva Dörrschuck and Ralf Tönjes (GenBank accession no.EU871587; E. Dörrschuck et al, unpublished data).…”
Section: Cells and Transfectionsmentioning
confidence: 99%
“…In contrast to the well-characterized A3-Vif interaction, still little is known about A3-neutralizing strategies used by retroviruses that do not encode a Vif protein. It has been reported that foamy retroviruses use the accessory protein Bet, and Human T-cell leukemia virus type I has evolved a unique nucleocapsid protein to counteract the packaging of cognate A3 proteins (12,44,58,71). The debate over the mechanism of resistance to murine A3 (muA3) of the rodent gammaretrovirus Moloney murine leukemia virus (Mo-MLV) has not come up with a generally convincing model, despite many studies (5, 9, 13, 32, 35, 49).…”
mentioning
confidence: 99%
“…29,30 In addition, we did not find a significant effect of Bet on the vector titer, as the 293T cells used for vector production are APOBEC3-deficient and thus, the deaminase-counteracting function of Bet is not required. 22 Additional effects of Bet on FFV vector particle release were not observed in this study.…”
Section: Discussionmentioning
confidence: 37%
“…The bel genes (Figure 1a) encode the viral Bel1/Tas transactivator and Bet that counteracts APOBEC3-mediated host restriction. 21,22 Importantly, only the env-bel-deleted vectors carrying SIN-deleted long terminal repressor (LTR) promoters turned out to be suited for the safe and long-term transduction of target cells.…”
Section: Introductionmentioning
confidence: 99%
“…The 3Ј regions in the minus-strand remain single-stranded for the longest time as they await plus-strand synthesis. This antiviral activity of human A3G also extends to other lentiviruses including simian immunodeficiency virus (SIV), equine infectious anemia virus (EIAV), and even distantly related retroviruses such as murine leukemia virus (MLV) and foamy viruses (6,29,31,34,35) Other Antiviral APOBEC3 Proteins Intriguingly, other APOBEC3 family members also exert antiviral activity. A3F induces dG to dA transitions in viral plus-strand DNAs, and its action is blocked by HIV-1 Vif (18, 36 -38).…”
Section: Mutagenesis By Virion-incorporated Apobec3gmentioning
confidence: 99%